1986
DOI: 10.1523/jneurosci.06-10-02889.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cell death of lumbosacral motoneurons in chick, quail, and chick-quail chimera embryos: a test of the quantitative matching hypothesis of neuronal cell death

Abstract: The quantitative matching hypothesis of neuronal cell death was tested for the chick hindlimb by determining the relationship between myotube number at the onset of motoneuron cell death and the number of motoneurons that survive in chicks, quail, and chick-quail chimeras. Hindlimb buds, which differ in size between the 2 species, were exchanged at stages 16 1/2-19, myosin ATPase-stained myotubes in selected thigh muscles were counted during the cell death period (stages 30-34), and lumbosacral motoneurons wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 58 publications
(80 reference statements)
6
48
0
1
Order By: Relevance
“…The posterior cardinal vein is formed at the level of the hindlimb by E3, as is the main artery of the early hindlimb, the ischiadic artery, as an offshoot of the dorsal aorta. Our data suggest that eight spinal segments, versus seven as reported by others (Tanaka and Landmesser, 1986a;Tyrrell et al, 1990), contribute to innervation of the quail hindlimb. Lumbosacral neurites reach the plexus region by E3.5 (HH21 & 22), pause for $24 hr, and then enter the hindlimb along with the ischiadic and crural arteries through shared foramina in the pelvic anlage.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The posterior cardinal vein is formed at the level of the hindlimb by E3, as is the main artery of the early hindlimb, the ischiadic artery, as an offshoot of the dorsal aorta. Our data suggest that eight spinal segments, versus seven as reported by others (Tanaka and Landmesser, 1986a;Tyrrell et al, 1990), contribute to innervation of the quail hindlimb. Lumbosacral neurites reach the plexus region by E3.5 (HH21 & 22), pause for $24 hr, and then enter the hindlimb along with the ischiadic and crural arteries through shared foramina in the pelvic anlage.…”
supporting
confidence: 72%
“…The present study found that eight spinal segments, as opposed to seven as reported by Tanaka and Landmesser (1986a) and Tyrrell et al (1990), contribute to the innervation of the quail hindlimb. During E4.0 (HH24) LS spinal nerves 1-8 continue to extend axons in distinct bundles towards the plexus region at the base of the hindlimb (Fig.…”
Section: Embryonic Day 40 (Hh24)supporting
confidence: 43%
“…The temporal pattern of eGFP ϩ cell death was remarkably similar to the normal time course in naturally occurring cell death (Hamburger, 1975;Tanaka and Landmesser, 1986). However, the extent of cell death was greater than the usual 50% loss in motoneurons.…”
Section: Transplanted Es Cell-derived Motoneurons Survive Beyond the supporting
confidence: 52%
“…Assuming a similar number of segmental motoneurons in segments S1 and S2, we estimate the total number of hindlimb motoneurons in the lumbar enlargement of the turtle to be at least 10,000. This is much lower than the estimated 60,000 lumbar motoneurons in humans (Tomlinson and Irving, 1977), but surprisingly similar to the number of hindlimb motoneurons in chicks (Hamburger, 1975;Laing, 1982;Tanaka and Landmesser, 1986). In contrast, the number of lumbar motoneurons is Ͻ2000 in adult bull frogs (Farel et al, 1992) and only 3500 in rodents (Oppenheim, 1986).…”
Section: Discussionmentioning
confidence: 57%